Fatty acids recovery from vegetable oil wet sludge by supercritical alcoholysis - Soto, G. (2013)
In the last decade the production of soybean and sunflower oil has greatly increased worldwide. Together with it, the market of the oil refining by-products, phospholipids sludge (wet gum) and distillates of the deodorizer (DDEO), is rapidly changing. In this work we propose to perform the direct alcoholysis of the phospholipids and oil enclosed in the wet gum using supercritical ethanol. A statistical design of experiments was performed to determine the effect of temperature (280-320 °C), alcohol to gum mass ratio(1 to 4 m/m),reaction time (20 to 50 min.) and water content (51 to 2.4 wt%). In all the studies a complete conversion of lipids was observed. After removal of volatile compounds, the reaction product contains an hexane insoluble solid substrate (around 25%) and an oily phase with more than 50wt% of fatty esters.